Federal policy, administration, and local good coming of age - Clark, Jill K., author; Jablonski, Becca B. R., author; Choices, publisher (Colorado State University. Libraries, 2018)
This article reviews the federal legislative and administrative maturation of local food. By focusing on the Farm Bill and the Know Your Farmer Know Your Food program—one way in which the USDA carries out its legislative mandates—we can assess where local foods will be in the future.
Keywords: agricultural and food policy; food consumption; nutrition; food safety